Mangrove gastropods as biomonitors for heavy metal contamination / Farhathul Manas - Farhathul , Manas (2021)
A process called biomonitoring can be used to analyze the factors that affect the ecosystem. In this study, gastropods and sediments were used to observeits impact on the study sites under the Klang Islands Mangrove Forest Reserve (KIMFR): Pulau Klang (Klang Island), Pulau Carey (Carey Island) and Telok Gong representing the natural mangrove, agricultural and industrial environments, respectively. Environmental monitoring was performed using gastropods and sediments that were collected and tested for heavy metals including arsenic (As), lead (Pb), cadmium (Cd), and mercury (Hg). The inductive coupled plasma mass spectrometry (ICP-MS) was used for heavy metal testing in gastropods whereas inductive coupled plasma optical emission spectrometry (ICP-OES) was used for sediment. The gastropods collected were observed to identify their species composition and abundance, and correlate heavy metals with the species. Telok Gong was found to be more diverse with nine species, followed by Carey Island and Klang Island with eight and five species respectively. Klang Island had less species richness, but more abundance. Ten gastropod species was discovered from the study sites: Nerita lineata, Cerithidea quadrata, Chicoreus capucinus, Telescopium telescopium (TG, KI & CI), Cassidula aurisfelis (TG & KI), Ellobium aurisjudae, Littorina scabra, Littorina melanostoma (TG & CI), Thais tissoti (CI), and Cerithidea cingulata (TG). Due to a scarce in availability and size, only six species were selected for heavy metal testing: Chicoreus capucinus, Telescopium telescopium, Nerita lineata, Cassidula aurisfelis, Cerithidea quadrata, and Ellobium aurisjudae. Concentration results of heavy metals from the separation of gastropod body and shell showed that As and Hg were more concentrated on the gastropod body whereas Cd and Pb were concentrated on the gastropod shell. Chicoreus capucinus showed a high concentration of As whereas Ellobium aurisjudae showed a higher concentration of Cd compared to other species. Cassidula aurisfelis showed a higher concentration of Pb where as Telescopium telescopium showed higher a concentration of Hg. It was assumed that these species could be used as biomonitors for specific metals. However, each species has its own ability to retain heavy metals hence, future studies for specific metals and gastropods should be conducted to confirm the species’ effectiveness as biomonitors. The heavy metal comparison showed As and Pb were more concentrated in sediments than in gastropods. However, the concentrations of Cd and Hg were similar which were < 0.5 μg/g in both gastropods and sediments. This may be due to the metals’ affinity towards the samples. The data comparison for the locations showed that Telok Gong had higher concentrations of As and Pb in both sediment and gastropod because it is surrounded by industries. However, Pb detected in gastropod at Klang Island showed higher value than Telok Gong. Sediment quality index (CBSOG SQG (2003) showed moderate pollution of As at Telok Gong and low pollution at the other sites. The values of Cd, Pb and Hg were relatively low for the three sites. The noticeable amount of As and Pb in gastropods indicate that the sites were polluted from adjacent areas like industries and shipping ports.